An improved equivalent energy-based design procedure for seismic isolation system of simply supported bridge in China's high-speed railway. Issue 134 (July 2020) - Guo, Wei; Du, Qiaodan; Huang, Zhe; Gou, Hongye; Xie, Xu; Li, Yong
Abstract: The high-speed railway (HSR) in China has developed rapidly in recent years. However, HSR bridges have to face the challenge of earthquakes since China is one of the most earthquake-prone countries in the world. Bearing is the key component in the HSR bridge, and using isolation bearing instead of common bearing (non isolation bearing) can provide bridge the better seismic performance. To improve seismic performance of HSR bridges at different earthquake intensities, in this paper the friction pendulum bearing (FPB) is used, and an improved equivalent energy-based design procedure (EEDP) based on the principle of energy conservation is proposed. This method has the advantages of simple calculation and avoiding complicated iterations, which can also take into account the post-yield stiffness of the structural members and is capable of designing three performance objectives simultaneously. Meanwhile, based on the analysis of experimental data, the improved performance objectives applicable to the isolated HSR bridges are proposed. The FPB of an isolated HSR bridge is designed by the improved EEDP to verify the applicability of the proposed method. Then the finite element model of the designed isolated HSR bridge is built, and nonlinear dynamic responses at different earthquake intensities are analyzed to examine the structural seismic performance. Results show that the designed structure can achieve the prescribed performance objectives at three earthquake intensities which proves the practicability and effectiveness of the proposed improved EEDP method. Highlights: The isolation bearing is adopted, which can reduce the seismic damage and minimize the downtime of HSR bridge. The improved performance objectives applicable to isolated HSR bridge are proposed based on the existing experimental data. The improved EEDP method for the series structural system is proposed and applied in the design of isolated HSR bridge.